INTEGRATION OF AQUACULTURE IN MARINE TOURISM DEVELOPMENT : A CASE STUDY IN BULUKUMBA REGENCY - Mia Rahayu; Yudha Sakti Pratama (Politeknik Pariwisata Makassar, 2025)
Aquaculture is a biological resource management activity aimed at meeting food needs, increasing community income, and conserving natural resources. Bulukumba Regency in South Sulawesi Province has significant potential in maritime tourism, with a coastal and marine area of ​​237.87 km² and a coastline of 128 km. However, the potential of these marine resources has not been optimally utilized as a leading tourism product. Currently, tourism activities in Bulukumba are still limited to conventional activities such as swimming, snorkeling, and diving, without considering the principles of sustainable tourism, which can actually increase negative impacts on the environment. This study aims to explore the possibility of integrating the concept of aquaculture as a leading sustainable tourism product in Bulukumba Regency and assess its suitability with local community activities and tourist behavior. The study used a case study method through observation and interviews. Observations were conducted on coastal community activities and tourist behavior, while interviews were used to explore potential collaboration between aquaculture and tourism activities. This study also reviewed government policies related to aquaculture and tourism management to assess their alignment. The research stages include preparation, data collection, analysis, interpretation of results, and report preparation. The research results indicate that aquaculture activities have the potential to be developed as an educational and conservation-based tourism product that can enrich the tourist experience while improving the well-being of coastal communities. Integrating aquaculture into the tourism sector could be a strategy for sustainable tourism development in Bulukumba. These findings are expected to serve as a reference for the local government in formulating policies and will be disseminated through publication in indexed national journals.